The geographical perspective of climate and its impact on the cultivation and production of summer vegetables in Al-Qadisiyah Governorate (Journal of Misan Researches, 2023)
Climate is the most important natural factor affecting the vegetation cover and the most controlling it and its distribution on the surface of the earth, as the human ability to control the climate is still very limited and is limited to reducing the influence of its elements and trying to adapt to it. The climatic requirements of each plant vary according to the stages of growth, and in general, vegetable crops are similar in their climatic requirements. Temperature and rain are among the most climatic factors affecting the distribution and growth of the plant, and if these requirements exceed the necessary maximum or decrease, they harm the plant. The areas planted with summer vegetables varied. In Al-Qadisiyah governorate, according to the years of study, it varies between the districts of the governorate, as Al-Diwaniyah district takes the first place with a percentage of (38.7%) of the total cultivated area in the governorate, followed by Afak district with a percentage of (33.8%), then Al-Hamza and Al-Shamiya districts with (20.4%, 7.1%) The research showed that there are positive and inverse relationships between the variables of temperature and rain with the production of summer vegetable crops in the study area during the study years, ranging between very weak and very strong.